Problematic screen exposure and oral health in preschool children: a comparison study - Şeyma Mustuloğlu; Özlem Tezol; Sıddıka Songul Yalcın (BMC, 2024)
Abstract Objectives Recent studies have highlighted the association between problematic screen exposure (PSE) in preschool children and various health issues. This study aims to determine the relationship between PSE and oral/dental health as well as parafunctional oral habits in this population. Methods Healthy children aged 3 to 6 years who visited the pediatric dentistry outpatient clinic were included in the study. PSE was evaluated using the parent-reported 'Seven-in-Seven-Screen-Exposure Questionnaire'. An intraoral examination was conducted to record the number of decated, missing, and filled teeth, along with scores from the International Caries Detection and Assessment System II (ICDAS II), as well as dental plaque and gingival indices. Results A total of 210 mother-child pairs were included in the study, comprising 70 pairs with PSE and 140 pairs without PSE. The sociodemographic characteristics, frequency of daily tooth brushing behaviors, use of children's toothpaste, and regular dental examinations were statistically evaluated between the PSE and non-PSE group (p > 0.05). Additionally, there was no statistically significant difference between the groups in terms of having abnormal oral habits (p > 0.05). In the PSE group, the median scores for gingival and plaque index were significantly higher (p = 0.011 and p = 0.006, respectively). The median number of decayed teeth was significantly higher in the PSE group (p = 0.039). Conclusions Turkish preschool children with PSE were found to have a significantly higher likelihood of experiencing poor oral health. Consequently, it is essential to conduct oral health examinations for Turkish preschool children exhibiting PSE. The study may have clinical implications for the evaluation of preschool children with problematic media use within dental practice.